2023
DOI: 10.1002/ps.7389
|View full text |Cite|
|
Sign up to set email alerts
|

Anti‐phytopathogenic activity and the mechanisms of phthalides from Angelica sinensis (Oliv.) Diels

Abstract: BACKGROUND: The resistance of traditional chemical fungicides to plant pathogenic fungi and the threats to the safety of humans and the environment highlight an urgent need to find safe and efficient alternatives to chemical fungicides. Owing to the wide spectrum of antifungal activities, low persistence and nontoxicity to mammals and aquatic life, essential oils have considerable potential as low-risk pesticides. In this study, the essential oil and the main components of Angelica sinensis (Oliv.) Diels (Dang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The antifungal activities of butylidenephthalide at 100 mg L −1 against Rhizoctonia solani , Sclerotinia sclerotiorum , F. graminearum , F. oxysporum and Magnaporthe oryzae are higher than that of ligustilide, but its bioactivity against B. cinerea is lower than that of ligustilide. The antifungal activities of butylphthalide at 100 mg L −1 against B. cinerea, F. graminearum , F. oxysporum and M. oryzae are higher than that of butylidenephthalide, but its bioactivity against R. solani and S. sclerotiorum is lower than that of butylidenephthalide 57 . These results indicated that the main antifungal active group of phthalides against different pathogens may be different.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The antifungal activities of butylidenephthalide at 100 mg L −1 against Rhizoctonia solani , Sclerotinia sclerotiorum , F. graminearum , F. oxysporum and Magnaporthe oryzae are higher than that of ligustilide, but its bioactivity against B. cinerea is lower than that of ligustilide. The antifungal activities of butylphthalide at 100 mg L −1 against B. cinerea, F. graminearum , F. oxysporum and M. oryzae are higher than that of butylidenephthalide, but its bioactivity against R. solani and S. sclerotiorum is lower than that of butylidenephthalide 57 . These results indicated that the main antifungal active group of phthalides against different pathogens may be different.…”
Section: Discussionmentioning
confidence: 88%
“…The antifungal activities of butylphthalide at 100 mg L −1 against B. cinerea, F. graminearum, F. oxysporum and M. oryzae are higher than that of butylidenephthalide, but its bioactivity against R. solani and S. sclerotiorum is lower than that of butylidenephthalide. 57 These results indicated that the main antifungal active group of phthalides against different pathogens may be different.…”
Section: Discussionmentioning
confidence: 97%
“…This result was in line with previously reported data in which 3-butylidenephthalid showed better antifungal activity against plant pathogenic fungi than ligustilide. 16 In addition, a previous study showed that the free hydroxyl group on the benzene ring could affect the antifungal effect of phthalides on plant pathogens. 38 Consistent with previous findings, the free hydroxyl group on the benzene ring could enhance the antifungal activity of phthalides (SENB, SENC versus 3-butylidenephthalide), but oxygen-containing substituents on the benzene ring decreased its antifungal activities (SENB, SENC versus synthesized analogs).…”
Section: The Antifungal Activities Of Phthalides In Vitro (Mics)mentioning
confidence: 99%
“…11 To date, only two phthalides (3-butylidenephthalide and 3-n-butylphthalide) have been reported to display antifungal activities against plant pathogenic fungi. 16 However, the antifungal effect, action mechanism, and structure-activity relationships (SRAs) of phthalides remain to be further explored and elucidated. In order to further explore the antifungal mechanism and SRAs of phthalides, the antifungal activities of five natural phthalides [senkyunolide B (SENB), senkyunolide C (SENC), ligustilide, 3-butylidenephthalide and 3-n-butylphthalide] from Angelica sinensis and four synthesized phthalide analogs (4-O-benzoyl-senkyunolide B, 4-O-methylsenkyunolide B, 5-O-benzoyl-senkyunolide C, and 5-O-methylsenkyunolide C) were evaluated against different human and plant pathogenic fungi in the current study (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In an article 1 titled ‘Anti‐phytopathogenic activity and the mechanisms of phthalides from Angelica sinensis (Oliv.) Diels’ by Yan‐Yan Ding, Yu Sun, Xiong‐Fei Luo, Shao‐Yong Zhang, Rui Wang, Zhi‐Gang Yang, Jing‐Ru Wang, Bao‐Qi Zhang, Zhi‐Jun Zhang, Yue Ma, Jun‐Xia An, Han Zhou and Ying‐Qian Liu (DOI: 10.1002/ps.7389), there were errors in Fig.…”
mentioning
confidence: 99%